The genome sequence of the Bog Ant Fly, Microdon myrmicae Schönrogge et al., 2002 [version 1; peer review: 2 approved] - Robert J. Wolton (Wellcome Open Research)
We present a genome assembly from a male specimen of Microdon myrmicae (Bog Ant Fly; Arthropoda; Insecta; Diptera; Syrphidae). The genome sequence has a total length of 1,366.18 megabases. Most of the assembly (99.91%) is scaffolded into 8 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled, with a length of 16.14 kilobases. Gene annotation of this assembly at Ensembl identified 13,398 protein-coding genes.